2017
DOI: 10.31219/osf.io/yt74g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motivation enhances control of positive and negative emotional distractions

Abstract: 2Using cognitive control to ignore distractions is essential for successfully achieving our goals. In emotionallyneutral contexts, motivation can reduce interference from irrelevant stimuli by enhancing cognitive control.However, attention is commonly biased towards emotional stimuli, making them potent distractors. Can motivation aid control of emotional distractions, and does it do so similarly for positive and negative stimuli?Here, we examined how task motivation influences control of distraction from posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In some of this work, motivation has been shown to interact with attentional processes, towards shared control over the processing of presented stimuli. For instance, Engelmann & Pessoa (2014) have demonstrated that the presence of reward can improve orienting and reorienting towards exogenous cues, at least in part through a sharpening of attention; and Walsh, et al (2018) have demonstrated that increased motivation can promote reduced distractibility from both positive and negative emotional stimuli (see also Padmala and Pessoa, 2014). In other work, the influence of motivation on resource allocation has been shown to be completely independent of attention, such that both motivation and attention invoke separate influence over stimulus reactivity (see Raymond, 2009;Raymond & O'Brien, 2009).…”
Section: A Motivational Framework For Psychopathymentioning
confidence: 99%
“…In some of this work, motivation has been shown to interact with attentional processes, towards shared control over the processing of presented stimuli. For instance, Engelmann & Pessoa (2014) have demonstrated that the presence of reward can improve orienting and reorienting towards exogenous cues, at least in part through a sharpening of attention; and Walsh, et al (2018) have demonstrated that increased motivation can promote reduced distractibility from both positive and negative emotional stimuli (see also Padmala and Pessoa, 2014). In other work, the influence of motivation on resource allocation has been shown to be completely independent of attention, such that both motivation and attention invoke separate influence over stimulus reactivity (see Raymond, 2009;Raymond & O'Brien, 2009).…”
Section: A Motivational Framework For Psychopathymentioning
confidence: 99%
“…33 We modified a well-validated cognitive task that assesses inhibitory control, in which participants are instructed to perform a cognitive task with emotionally or motivationally salient stimuli as distractors. 34 In the current study, we assessed inhibitory control over gaming-related distractors after tDCS. We also assessed background and cue-induced cravings before and after tDCS.…”
Section: Clinical Trials No: Nct03352973mentioning
confidence: 99%
“…On the other hand, there are many more studies on the positive correlation between motivation and attention. For example, motivation as a reward influences the improvement of distraction control [13].…”
Section: Introductionmentioning
confidence: 99%